Performing the Void: The Violence of the Unassimilated in Some Contemporary British Narratives - Jean-Michel Ganteau (Sillages Critiques)
The article addresses aspects of the vulnerable text and of textual vulnerability as expressed in fictional representations of trauma. More specifically, it focuses on the violence of a writing that swells up to indirectly evoke and perform the unbearable and unassimilated traumatic event. To do so, it concentrates on the paradox according to which the extremum of textual matter is solicited the better to privilege the powers of metalepsis. The modalities of such violent writing are indexed on rhythmical effects whose purpose is to perform an absence, an inaccessibility and a compulsion to repeat that find their origin in the category of belatedness. The vulnerable text is vulnerable, precisely, because it opens up to that which is not said or known, because it is dependent on presenting that which it can only keep silent, and in so far as it becomes a rhetorical or figural symptom, expressing and performing some heteronomy to the wound. Ultimately, the article concentrates on the figure of the archive that performs yet another violence by dramatising the possibility of evoking the void at the origin of trauma through its very impossibility.